Axonal transport dynamics explain directional bias in tau deposition. (December 2021) - Torok, Justin; Maia, Pedro D.; Verma, Parul; Mezias, Christopher; Raj, Ashish
Abstract: Background: Emerging evidence indicates that defects in axonal transport, an early feature of AD pathology 1, could play a role in how directional biases develop on regional level 2 . Specifically, kinesin‐1, a motor protein responsible for the anterograde‐directed transport of axonal cargoes including tau, is dysregulated by hyperphosphorylated tau species 3, 4 . Here we demonstrate that a mathematical model of tau‐modified axonal transport can reproduce directional biases in tauopathy spread observed in mouse models of disease. Methods: We implemented a mathematical model incorporating the effects of aggregation and fragmentation of pathological tau complexes of two types, soluble and insoluble, on axonal transport and diffusion. We simulated the spatiotemporal profiles of each tau species in a multicompartment, two‐neuron system using biologically plausible parameters and time scales. Notably, anterograde axonal transport velocity is modeled as being locally enhanced by the presence of soluble pathological tau 3 and hindered by insoluble tau 4 . Results: We find that changing the balance of tau transport feedback parameters can elicit anterograde and retrograde biases in the distributions of soluble and insoluble tau between somatodendritic compartments in our two‐neuron system (Figures 1 & 2). Changing the aggregation and fragmentation parameters perturbs this balance, suggesting complex interplay between these distinct molecular processes (Figures 3 & 4). The model also recreates spread biases comparable to those derived from network spread using AD‐like and non‐AD‐like mouse tauopathy models 2 (Figure 5). Conclusion: Our model of tau axonal transport feedback provides a parsimonious, biologically plausible explanation for apparent directionality observed in mouse model tauopathy spread, linking microscopic differences in tau conformational states and variance in clinical presentation. References: (1) Wang, Z.‐X., Tan, L. & Yu, J.‐T. Axonal Transport Defects in Alzheimer's Disease. Mol Neurobiol 51, 1309–1321 (2015). (2) Mezias, C. & Raj, A. The role of directionality in determining spatiotemporal tau pathology differs between AD‐Like and Non‐AD‐Like mouse models. bioRxiv 11.06.371625 (2020) doi:10.1101/2020.11.06.371625. (3) Rodríguez‐Martín, T. et al . Tau phosphorylation affects its axonal transport and degradation. Neurobiology of Aging 34, 2146–2157 (2013). (4) Sherman, M. A. et al . Soluble Conformers of Aβ and Tau Alter Selective Proteins Governing Axonal Transport. J Neurosci 36, 9647–9658 (2016).